2019
DOI: 10.7759/cureus.4310
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Cobalamin Deficiency and Macrocytic Anemia Secondary to Sunitinib

Abstract: Sunitinib is an oral tyrosine kinase inhibitor (TKI) commonly used in the treatment of renal cell carcinoma (RCC). Among a broad range of toxicities, anemia and macrocytosis are common in patients treated with sunitinib. Correlation between sunitinib-associated macrocytosis and cobalamin deficiency has been reported in small case series and retrospective analyses, although others have not found an association. Here, we present a case of transfusion-dependent macrocytic anemia with cobalamin and folate deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…These events may be present coincidentally. Initial observations published by Gillessen and Billemont [ 19 , 27 ] and supported by another case report by Reed et al [ 20 ] suggested a connection between absolute or relative vitamin B12 deficiency and sunitinib-related macrocytosis. However, these observations were performed on a limited number of patients.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These events may be present coincidentally. Initial observations published by Gillessen and Billemont [ 19 , 27 ] and supported by another case report by Reed et al [ 20 ] suggested a connection between absolute or relative vitamin B12 deficiency and sunitinib-related macrocytosis. However, these observations were performed on a limited number of patients.…”
Section: Discussionmentioning
confidence: 73%
“…It has been reported that sunitinib and several other tyrosine kinase inhibitors influence the erythrocyte mean corpuscular volume parameter (MCV) [ 17 , 18 ]. Initial considerations about this phenomenon included possible relative folate and cobalamin deficiency [ 19 , 20 ]. However, more recent studies provided data that this effect is related to the inhibitory activity of tyrosine kinase inhibitors towards c-KIT, which is extensively expressed by progenitor cells in the bone marrow [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these mechanisms, the most prevalent is the occurrence of point mutations at the tyrosine kinase's binding site, resulting in a diminished affinity for TKIs. Given that TKIs necessitate prolonged administration, non-compliance with the prescribed treatment regimen is one of the foremost reasons for diminished efficacy [12].…”
Section: Discussionmentioning
confidence: 99%